A Mini-Review on the Phytochemistry and Pharmacology of the Plant Carica Papaya L. (Caricaceae) - Clement Inkoto Liyongo; Colette Masengo Ashande; Clarisse Falanga Mawi; Blaise Membo wa Mbembo; Jean-Jacques Amogu Domondo; Mahendra Ilmi S Matondang; Jean-Pierre Kayembe Kayembe; Pius Tshimankinda Mpiana; Koto-te-Nyiwa Ngbolua (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Medicinal plant is an important element of indigenous medical systems all over the world. The ethno botany provides a rich resource for natural drug research and development. Carica papaya is used in Traditional Medicine since a long time. Our investigations started by a search of relevant literature on the plant species. Databases such as Science direct, PubMed, Google Scholar and Scopus were used successively to retrieve the articles on C. papaya. The chemical structures of isolates compounds from this plant were drawn using ChemBioDraw Ultra 12.0 software package. Finally, bibliographical references were made using bibliographical software "Mendeley". Results show that the plant C. papaya contains various secondary metabolites, minerals and vitamins. The plant species is reported to possess various pharmacological properties like anti-oxidant, anti-inflammatory, antibacterial, anti-diabetic, anti-hyperlipidemic, larvicidal effects, etc. These pharmacological activities could due to the presence of various phytochemicals present in this plant species. The present review can therefore help inform future scientific research towards the development of novel drugs of relevance from C. papaya to combat various ailments including Sickle cell disease.